If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6(m + 18) = 66 Reorder the terms: -6(18 + m) = 66 (18 * -6 + m * -6) = 66 (-108 + -6m) = 66 Solving -108 + -6m = 66 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '108' to each side of the equation. -108 + 108 + -6m = 66 + 108 Combine like terms: -108 + 108 = 0 0 + -6m = 66 + 108 -6m = 66 + 108 Combine like terms: 66 + 108 = 174 -6m = 174 Divide each side by '-6'. m = -29 Simplifying m = -29
| -9x+y=55 | | k(x)=10x+5 | | 5n=214 | | y+6=1(x-9) | | 4x-6+6=4x+6 | | 8x+15=87 | | 2x+(3x-4)=4x-4 | | 6x-9=24+3 | | w-100=840 | | 2x+4y^2-16=0 | | 2x+(3x-4)=1x-4 | | 13n=8n-33-6n | | -154.16+4c=x | | 9x+7=31+2x | | 2x+(3x-4)=-4x-4 | | 38.54+0.25x=c | | 4x^2-18x+10=0 | | 8x+5y=285 | | 2x+(-8)=-16 | | x+9=-35 | | x^2+34x+81=0 | | 3x^2=220-2x^2 | | k+751=3456 | | 100x=4500 | | A(3)+B(8)+C(-4)=D | | -30=-10b | | 4xsquared+6=-11 | | 3x-8=27+8 | | 7=4m-2m+1 | | w+100=823 | | [x+2]+8=13 | | 7g+14-5g=14 |